Optimization of secreted recombinant human epidermal growth factor production using pectate lyase B from Escherichia coli BL21(DE3) by central composite design and its production in high cell density culture - Sriwidodo Sriwidodo; Toto Subroto; Iman P Maksum; Nasrul Wathoni; Tina Rostinawati; Himmatul Ulya; Indah U Putri (Wolters Kluwer Medknow Publications, 2019)
Context: Human Epidermal Growth Factor (hEGF) is a potential therapeutic protein that has been widely used as a healing agent for various chronic wounds. It induces the proliferation and metabolism of epithelial cells, regenerates skin cells, and validates skin elasticity. In the previous study, recombinant hEGF (rhEGF) had been successfully expressed extracellularly in Escherichia coli (E. coli) BL21 (DE3) using pectate lyase B (PelB) signal peptide. The previous study has shown that the medium concentration and the induction time influenced the production of rhEGF. Aims: Therefore, this study was conducted to optimize the induction time and medium concentration for rhEGF extracellular secretion then followed by scale-up production. Settings and Design: This experiment was carried out using E. coli BL21 (DE3) which contains pD881 plasmid that carries hEGF and PelB gene. Optimization design of induction time and medium concentration were obtained using Central Composite Design (CCD). Methods and Material: The method of study started by the rejuvenation of E. coli culture, extracellular secretion, and optimization in the flask scale then followed by scaled-up production with high-cell density culture in the fermenter. Statistical analysis used: The optimization was carried out using Response Surface Methodology (RSM) and multi regression analysis. Results: This work showed that the multiplication of 1.5-fold medium concentration with induction time 3h after the culture started gave the best result among another condition in this study. Additionally, the rhEGF production in the fermenter scale was identified by SDS-PAGE Tricine and quantified by ELISA, which showed 122.40 μg of the rhEGF per milliliter medium. Conclusions: In respect of the result, we conclude that the optimized condition of extracellular secretion was successfully obtained, and gives higher result before the previous study.